PEMANFAATAN INSTAGRAM SEBAGAI KONTEN MEDIA PEMBELAJARAN MICROBLOG DALAM JARINGAN PADA MATA KULIAH TEKNOLOGI MULTIMEDIA - Ahmad Almukaroma Liow; Sitti Suhada; Nikmasari Pakaya (Universitas Negeri Gorontalo, 2021)
AbstractCovid-19 is a pandemic that lasted from early 2019 to 2021, and it's unclear how it was followed. The thing that causes the tension of the learning process at school and eventually the learning is carried out at home. Many ways that can be used as part of innovative learning models, one with the use of instagram as a developed tool for off-school learning. Using each of these features on lnstagram makes a blog microblog to develop as a network learning medium to support the learning process. The study is a qualitative descriptive study with fieldresearch (field reseaech), a method of field research that enables respondents directly to obtain data or information. Research shows that the use of instagram as content of microblogging on a network with an 86% presentation means that the use of instagram can be put to good use by students as learning content.